Hippolytia gossypina (Hook. f. & Thoms. ex C. B. Clarke) Shih and Lactuca decipiens C. B. Clarke (Asteraceae): New Records for West Bengal - Garg , Arti (Rheedea, 2006)
Hippolytia gossypina (Hook. f. & Thoms. ex C. B. Clarke) Shih and Lactuca decipiens C. B. Clarke are reported for the first time from West Bengal.